2016
DOI: 10.1016/j.jclepro.2016.07.186
|View full text |Cite
|
Sign up to set email alerts
|

Cost, energy and emissions assessment of organic polymer light-emitting device architectures

Abstract: B f lm/W luminous efficacy Electrical-to-optical power conversion efficiency k 0.75 correction factor Accounts for device operation at 75% of its initial luminous efficacy, on average, due to degradationand efficiency roll-off during its operational lifetime B cd/m 2 luminance Used to quantify the brightness of a lightemitting deviceper area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
0
13
0
2
Order By: Relevance
“…Paper 13 (Carter et al, 2016). : The authors investigated Organic Light Emitting Diodes (OLEDs) as alternative display and lighting options that have the potential for lower fabrication costs, greater versatility, and lower power consumption costs when compared to more traditional options, such as blue inorganic LEDs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper 13 (Carter et al, 2016). : The authors investigated Organic Light Emitting Diodes (OLEDs) as alternative display and lighting options that have the potential for lower fabrication costs, greater versatility, and lower power consumption costs when compared to more traditional options, such as blue inorganic LEDs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A number of improvements were identified to make P-OLEDs competitive in terms of operating cost, and energy and environmental impacts relative to traditional inorganic LEDs. Those improvements relate to electrical-to-optical power conversion efficiency and to extending the operational lifetime of the P-OLED (Carter et al, 2016). Comparison of various polymer-based OLEDs device architectures showed that the top-emitting inverted P-OLED is likely to be the most promising device architecture to pursue in terms of achieving operational lifetimes, device costs and efficiencies that are competitive with the blue inorganic LEDs and to achieving fullysolution processed large-scale manufacturing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The widely used indium tin oxide (ITO) electrode represents almost half of the cost of an OLED device or an OPV device. [26][27][28][29] Carter et al revealed that the cost of a top-emitting OLED represents only 60% of the cost of a bottom-emitting OLED since the top-emitting OLED is ITOfree. 26 ITO must be substituted by less costly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Os OLEDs comerciais baseados em pequenas moléculas disponíveis atualmente são fabricados por deposição térmica em alto vácuo, tornando-os caros [8]. Assim, para que estes dispositivos sejam comercialmente competitivos, novas técnicas de deposição de baixo custo e de grande escala devem ser desenvolvidas [8].…”
Section: Lista De Figurasunclassified
“…Os PLEDs vêm sendo muito estudados como uma promessa de trazer esta versatilidade no processo de deposição dos filmes finos uma vez que as principais técnicas envolvidas são de baixo custo e de baixo consumo de energia, pois são baseadas em soluções como, por exemplo, ink-jet printing, spin coating, blade coating e assim por diante [2]. Entretanto, estes dispositivos apresentam baixa eficiência luminosa e curto tempo operacional de vida, principalmente, os PLEDs com emissão azul comparado aos PLEDs com emissão no vermelho e verde, dificultando a comercialização de full color displays e sistemas de iluminação [8].…”
Section: Lista De Figurasunclassified